2020
DOI: 10.1016/j.jmpt.2019.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Physical Activity, Weight Loss, Anxiety, and Lumbopelvic Pain in Postpartum Women

Abstract: Background: Lumbopelvic pain (LBPP) affects 45-81% of pregnant women, and 25 to 43% of these women report persistent LBPP beyond 3 months after giving birth. The objective of this study was to investigate the association between physical activity, weight status, anxiety and LBPP symptoms evolution in postpartum women.Methods: This is a prospective observational cohort study with 3 time point assessments (baseline (T0), 3 months (T3) and 6 months (T6) later). Women with persistent LBPP 3 to 12 months after deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In this study, it was found that pain was felt in the leg, abdomen, waist, chest, knee, hip and perineum region in the postpartum period, and that the majority of puerperal women experienced severe pain in the low back, perineum and head region. It was stated that 25-68 % of women experience low back pain in the postpartum period [13]. In this study, it was determined that 46.4 % of puerperant women had severe low back pain and 29 % had moderate low back pain.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In this study, it was found that pain was felt in the leg, abdomen, waist, chest, knee, hip and perineum region in the postpartum period, and that the majority of puerperal women experienced severe pain in the low back, perineum and head region. It was stated that 25-68 % of women experience low back pain in the postpartum period [13]. In this study, it was determined that 46.4 % of puerperant women had severe low back pain and 29 % had moderate low back pain.…”
Section: Discussionmentioning
confidence: 83%
“…Studies showed that those who delivered by cesarean section experience more pain [10], and vaginal delivery is more disadvantageous on postpartum chronic pain than cesarean section [11]. However, it is stated that the baby's weight, mother's age, education level and mood during pregnancy are effective factors on the postpartum pain perception experience [12], and that physical activity has a positive effect on the postpartum pain perception experience [13]. It is stated that maternal self-confidence is affected by factors such as being educated about baby care, having experience in baby care, and feeling ready for the role of motherhood, and that mothers need information in this special period [8,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale behind the hypothesis is that, among the general population, greater BMI and central obesity are associated with greater pain intensity and chronic pain 12,13 . In addition, obesity is associated with increased pain sensitivity 14,15 , and weight loss has been shown to reduce some types of chronic pain 16,17 . As noted by Nowak et al: "a metabolic hypothesis of pain in obesity has gained increasing support as an important mechanism contributing to pain" 18 .…”
mentioning
confidence: 99%
“… 12 , 13 In addition, obesity is associated with increased pain sensitivity, 14 , 15 and weight loss has been shown to reduce some types of chronic pain. 16 , 17 As noted by Nowak et al, “a metabolic hypothesis of pain in obesity has gained increasing support as an important mechanism contributing to pain.” 18 This observation led Nowak et al to examine the potential implications of this association for understanding pain in ADPKD patients in particular.…”
mentioning
confidence: 99%